Mapping of priority areas for environmental recovery of Rio Pomba city, Minas Gerais - Oliveira, Jaqueline Aparecida de; Silva, Jeniffer Barroso da; Ribeiro, Kleber Mariano; Ferreira, Flávia Monteiro Coelho; Silva, Roselir Ribeiro da (Revista Brasileira de Geografia Física, 2020)
The present paper aimed to map the priority areas for environmental recovery of Rio Pomba city, Minas Gerais, as part of the creation of a strategic plan for environmental actions. In order to carry out the proposed approaches, the information layers (IL) geology, climate, land use, pedology and geomorphology of study area were mapped individually and transformed, by multicriteria analysis, in a single database using the geographic information system (GIS), resulting in the mapping of natural vulnerability to soil loss. The results showed that areas vulnerable to erosion processes, and priority to environmental restoration actions, were concentrated in declivity regions of study area, while regions classified as stable accumulated in permanent preservation areas (PPA) marginal to water resources. These results diverged from the field observations and the addition of an IL that demarcates the PPAs in multicriteria analysis was proposed as alternative. The new results were satisfactory, closer to the field inspections and this new methodology can be used in management of environmental restoration actions of city, in which should begin with the marginal PPAs and in the northern region.